SUPREME COURT REGULATION (PERMA) NUMBER 1 YEAR 2020: SOLUTIONS IN THE GUIDELINES FOR DETERMINING DEATH PENALTY FOR CORRUPTION CRIMINAL ACTS IN CERTAIN CONDITIONS - Mar’ie Mahfudz Harahap; Reski Anwar (STIH Putri Maharaja, 2022)
The sanctioning of Supreme Court Regulation No. 1 of 2020 in the time of Covid-19 opens a new glimmer of hope in corruption cases in certain circumstances in ndonesia. This regulation provides guidelines for judges in providing the death penalty for corruptors. The motivation behind the Research is to see how the sentencing guidelines in dropping the death penalty to corruptors in certain circumstances, and to understand how the view of the study concepts and comparative of the death penalty for corruptors. This research is included in the normative legal research section using primary and secondary legal materials. The approach used is a statute approach, comparative approach, and conceptual approach. This research is included in the normative juridical research with the method of statutory, concept, and comparison approach. The results of study, it appears that the death penalty is only for corruption crimes by weighting and threatened alternatively, and may be dropped when considering the high level of guilty, impact, and profit while in comparison.